WANPRESTASI TERHADAP PELAKSANAAN PERJAJIAN KONTRAK ANTARA PEMILIK PROYEK DENGAN KONTRAKTOR - irwan; Rasdianah; Umar P (Unisan Law Review, 2025)
Default in the implementation of the work contract agreement between the project owner and the contractor is inaccuracy in drafting the contract clauses and the inability of the parties to comply with the contents of the contract clauses so that the parties are unable to take responsibility for implementing the clauses because they are considered unprofitable. Things that can cause default are: (a). There are changes to the construction plans from the project owner that are not in accordance with the contract clauses so that the contractor must bear the burden of costs and time for changes to the contract clauses. (b). The project owner is unable to make payments and repay project services to the contractor, while the contractor is unable to carry out its obligations in completing the development project properly and on time. For To minimize losses due to default between the project owner and contractor, the contract agreement is accompanied by a document guarantee equivalent to the contract value. The project owner and contractor must prepare a document guarantee with a minimum value equal to the value of the project and this guarantee is held by a third party, namely an official state agency, so that if there is a default by one of the parties, the confiscated document guarantee will be handed over to the party concerned. disadvantaged. The factors that can cause a default on the work contract agreement between the project owner and the contractor are: (1) Negligence Factor: Negligence committed by one or both parties, namely not fulfilling the achievements at all, the achievements made are imperfect, late. fulfilling achievements, doing what is in the agreement beyond what was promised, (2). Cost Overrun Factor: Cost overruns cause the project owner to be unable to make payments to the contractor and the contractor to be unable to complete the work.